Towards a Grounded Theory of Mid-Career Stuckness - Iben Treebak; Rie Thomsen (Nordic Journal of Transitions, Careers and Guidance, 2022)
This paper explores the phenomenon of mid-career stuckness through a grounded theory approach to the analysis of in-depth qualitative interviews with five life science professionals in the midst of their career. The study shows that career stuckness is an emotion, a long-lasting, complex sense of professional unfulfilment and stagnation in a job or career path. At the same time, however, it is also a situation, in that the individual is subject to labour market conditions and discourses regarding successful or expected career development – external circumstances which they cannot control, but to which they must actively relate. The experience of career stuckness is rooted in corporate and labour market structures and an understanding of ‘a good career’ as a linear and upward process. Abstrakt Denne artikel undersøger fænomenet fastbrændthed. Artiklens analyse bygger på grounded theory og analyserer dybdegående, kvalitative interview med fem life science akademikere midt i karrieren. Studiet viser, at fastbrændthed i karrieren er en emotion; en langvarig, kompleks oplevelse af faglig uforløsthed og stagnation i et job eller et karrierespor. Samtidig er det en situation; idet individet er under indflydelse af vilkår på arbejdsmarkedet for mennesker midt i karrieren, og påvirket af diskurser om, hvad der udgør succesfuld karriereudvikling. Det er ydre omstændigheder, som de ikke kan styre, men som de må forholde sig aktivt til. Fastbrændthed er forbundet til forståelse af ‘en god karriere’, som en lineært opadgående proces, og til arbejdsmarkedsstrukturer og lokal organisering i virksomheder.